Comparing item parameter estimates and fit statistics of the Rasch model from three different traditions - Bahrul Hayat; Muhammad Dwirifqi Kharisma Putra; Bambang Suryadi (Graduate School, Universitas Negeri Yogyakarta, 2020)
Rasch model is a method that has a long history in its application in the fields of social and behavioral sciences, including educational measurement. Under certain circumstances, Rasch models are known as a special case of Item response theory (IRT), while IRT is equivalent to the Item Factor Analysis (IFA) models as a special case of Structural Equation Models (SEM), although there are other ‘tradition’ that consider Rasch measurement models not part of both. In this study, a simulation study was conducted using simulated data to explain how the interrelationships between the Rasch model as a constraint version of 2-parameter logistic (2-PL) IRT, Rasch model as an item factor analysis were compared with the Rasch measurement model using Mplus, IRTPRO and WINSTEPS program, each of which came from its own 'tradition'. The results of this study indicate that Rasch models and IFA as a special case of SEM are mathematically equal, as well as the Rasch measurement model, but due to different philosophical perspectives, people might vary in their understanding of this concept. Given the findings of this study, it is expected that confusion and misunderstanding between the three can be overcome.